(3CQLhRI aj UMI GdCLSGOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3jbhd QGLi QHg Gjf SjfG hde jRd HGddg eSJYjfG jG SGFdi Yf UMI GdCLSGO GSeY UMjM GdWH HGdESfGO s
(3BNQgG (B:s
(3hTGgO GdCYVGA ai GdGfSGf jfWb HGdZjH HdG dSGf acja dG JTgO ai GdbjeI Ydjc EP dG JfaY GdfOGeI s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B14 s
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI jMji HGTG GdLdjdi (B- (3GdehUd (B(236) s
Keywords: (3GdWHs